Analisis Dampak Covid-19 terhadap Ekonomi Masyarakat Desa Lamgugob - Zulia Findayani; Zahriah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The Covid-19 pandemic has forced people to reduce their activities outside the home. This has hampered many community activities, including buying and selling transactions and other work. This creates new problems in the form of economic difficulties experienced by the community. This study aims to determine how big the impact of Covid-10 on the economic aspects of the Lamgugo village community. This research was conducted using quantitative descriptive methods, data collection techniques in the form of questionnaires and qualitative descriptive data analysis techniques. Through this research, it was found that as many as 65% of the entire Lamgugo village community experienced economic difficulties in the midst of the Covid-19 pandemic.